Participation in Types of Physical Activities Among US Adults—National Health and Nutrition Examination Survey 1999–2006 - Dai, Shifan (J Phys Act Health, 2015)
BACKGROUND: Information on specific types of physical activities in which US adults participate is important for community and program development to promote physical activity. METHODS: Prevalence of participation and average time spent for 33 leisure-time aerobic activities and 10 activity categories were calculated using self-reported data from 22,545 participants aged ≥ 18 years in the National Health and Nutrition Examination Survey 1999–2006. RESULTS: Overall, 38% of US adults reported no leisure-time physical activities, and 43% reported 1 or 2 activities in the past 30 days. Walking was the most frequently reported activity for both men (29%) and women (38%). Among walkers, the average time spent walking was 198 minutes/week for men and 152 minutes/week for women. The most reported activities for men after walking were bicycling and yard work, and for women were aerobics and dance. For most activity categories, participation was lower among adults aged ≥ 65 years than among younger adults, and among Mexican Americans and non-Hispanic blacks than among non-Hispanic whites. Participation in most categories increased with increasing educational attainment. CONCLUSIONS: Participation in physical activity differs by types of activities and demographic characteristics. Physical activity promotion programs should take these differences into account when developing intervention strategies.